Sensation, perception and the aging process - Colavita, Francis B.; The Teaching Company (Chantilly, VA : The Teaching Company, 2006)
Professor Francis Colavita offers a biopsychological perspective on the way we humans navigate and react to the world around us in a process that is ever-changing. Our experiences are vastly different today than they were when we were children and our senses and brains were still developing; and those experiences are becoming ever more different as we age, when natural changes alert us to the need to compensate, often in ways that are quite positive
Part 1. Lecture 1. Sensation, perception, and behavior -- Lecture 2. Sensation and perception--a distinction -- Lecture 3. Vision--stimulus and the optical system -- Lecture 4. Vision--the retina -- Lecture 5. Vision--beyond the optic nerve -- Lecture 6. Vision--age-related changes -- Lecture 7. Hearing--stimulus and supporting structures -- Lecture 8. Hearing--the inner ear -- Lecture 9. Hearing--age-related changes -- Lecture 10. The cutaneous system--receptors, pathways -- Lecture 11. The cutaneous system--early development -- Lecture 12. The cutaneous system--age-related changes --Part 2. Lecture 13. Pain--early history -- Lecture 14. Pain--acupuncture, endorphines, and aging -- Lecture 15. Taste--stimulus, structures, and receptors -- Lecture 16. Taste--factors influencing preferences -- Lecture 17. Smell--the unappreciated sense -- Lecture 18. Smell--consequences of anosmia -- Lecture 19. The vestibular system--body orientation -- Lecture 20. The kinesthetic sense--motor memory -- Lecture 21. Brain mechanisms and perception -- Lecture 22. Perception of language -- Lecture 23. The visual agnosias -- Lecture 24. Perception of other people/course summary
Title from title screen
Lectures delivered by Professor Francis B. Colavita, University of Pittsburgh
Keywords: Senses and sensation; Senses and sensation in old age; Perception